Public Service Satisfaction Licensing in Deli Serdang Regency - Nufaris Elisa (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2020)
This study aims to determine the satisfaction of public service in the field of licensing Deli Serdang regency. Location of the research conducted in the area of Deli Serdang regency government is the reason for this is a site selection study for Deli Serdang regency. This study uses secondary data sources as the primary data source, which is equipped with a primary data source as a supporter. Sources of data mainly obtained from the Department of Commerce Office of P2KPM and Deli Serdang regency. The results showed that people's satisfaction of public services in Deli Serdang regency values obtained cumulative index of 21.7 in the range of 17-23 (moderate), so it can be concluded that the implementation of public service in Deli Serdang Regency included in the rate being.